The time-course of information alignment. - Denise Moerel (9080849) (2025)
(A) The time-course of information alignment is shown in dark blue. This measure was obtained by collapsing the temporal generalization matrix of dissimilarity matrix correlations between the two individuals in each pair (Fig 2) along one of the time dimensions. Cluster corrected p values <.05 for this correlation are shown in dark blue below. The shaded area shows the 95% confidence interval. The time-course of dissimilarity matrix correlations for the randomly matched pseudo-pairs is shown as a dashed light blue line. This shows the information alignment that is driven by sensory-evoked signals. Cluster corrected p values <.05 for the difference between the real and pseudo-pairs are shown in red below. This shows the information alignment that was not driven by sensory-evoked signals. The topographies for the information alignment are shown below the plot. They show the average correlation of one channel with all channels for the other participant, averaged across 100-ms time bins. The top row shows the topographies for the real pairs, the middle row for the pseudo-pairs, and the bottom row for the contrast (real—pseudo-pairs). (B) The channels included in the six clusters: Frontal Left (F L), Frontal Right (F R), Temporal/Central Left (TC L), Temporal/Central Right (TC R), Parietal/Occipital Left (PO L), and Parietal/Occipital Right (PO R). (C) The dissimilarity matrix correlations between person A (left) and person B (right) in the pair, for all combinations of six channel clusters. Correlations are averaged across an early (45–150 ms) and late (200–1,000 ms) time-window. The color of the lines reflects the strength of the correlation, with darker color reflecting stronger information alignment. The left plots show the correlation within real pairs, the middle plots show the correlation for the pseudo-pairs, and the right plots show the difference between real and pseudo-pairs.